EFL Pre-service Teachers' Perspectives on Team-based Project in Developing English Lesson Plans in Primary Teacher Program - Apoko, Tri Wintolo (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2024)
Team-based project (TBP) has been implemented in some universities to encourage students to be creative and motivated to develop some projects. However, not all EFL teachers in higher education can effectively apply TBP in generating the projects, including English instructional tools for young learners developed by EFL pre-service teachers. This study examines the EFL pre-service teachers' perspectives on using TBP in the contexts of how English lesson plans are developed, their creativity, motivations, and learning opportunities in the primary school teacher education program (PSTEP). The participants of this study are EFL pre-service teachers of PSTEP in one of the reputable private universities in Jakarta, Indonesia, who attended an English Learning in Primary Schools course in the second semester. This study uses a mixed methods design for collecting data from the survey and data from interviews. The results showed that EFL pre-service teachers had positive perceptions of using TBP in developing English lesson plans. The results also demonstrated that EFL pre-service teachers’ creativity, motivation, and learning opportunities, qualitatively increased. Thus, this study recommends that EFL pre-service teachers continually work in groups to discuss and share their critical ideas with their teammates to produce English lesson plans as projects.